Digital media consumption from childhood to pre-adolescence: the research-action "One Bit at a Time" in Italy for Digital Education among children/teachers and families - Lugaro, Gabriele; Ferro, Jacopo; Di Bari, Cosimo (Studi sulla Formazione/Open Journal of Education, 2024)
The article outlines the results of a research and training project that examined the habits and patterns of digital device usage among 1,014 families with children aged 0-6 years and 7-11 years in the Liguria region. It analyzes the trends and developments in media consumption of smartphones, tablets, TVs, and video game consoles during the transition from preschool to elementary school. The project was conducted under “One Bit at a Time,” an initiative promoted by the school in Finale Ligure. It involved families and teachers from the provinces of Savona, Imperia, and Genoa and featured quantitative data collection along with a training course aimed at teachers, as well as a question-and-answer session for families. Both training sessions employed a problematizing approach to explore the effects and functionality of digital devices and social media on children and adolescents, aiming to raise adult awareness about the necessity of incorporating Media Education and Digital Education activities from early childhood. The findings underscore the importance of shared responsibility among adults, both at home and school, to foster a positive engagement with digital media that enhances children’s cognitive and exploratory skills.